(untitled) (Symposium on Life and Environmental Sciences, 2026)
The article analyses the principal models of contemporary lexicography and describes the new dictionary types that have emerged where corpus linguistics, digital technology and cognitive research meet. The classical accounts of L.V.Shcherba, V.V.Morkovkin, Y.N.Karaulov, P.N.Denisov, V.A.Kozyrev and V.D.Chernyak are read against foreign work in electronic lexicography by S.Granger, M.Paquot, B.T.S.Atkins, M.Rundell, P.Hanks, A.Kilgarriff, H.Bergenholtz and S.Tarp. Corpus-based, associative, ideographic, active and learner dictionaries receive close attention, together with the resources of the Russian National Corpus, the Sketch Engine query system, and the Uzbek tradition represented by the five-volume Izohli lugʻat of 2006 to 2008.